FIECO-R4-101: Development of Hazard Detection System for Shrimp Survival - Aziz, Nazrina; Misiran, Masnita; Mahat, Nor Idayu; Mat Yusof, Muhammad; Ruddin, Amir Shah; Razi, Mohd Afiq (2016)
This paper discusses the development of an analytical system to monitor the survival of shrimp at the iKERPAN fully integrated aquaculture park, located at the Kuala Kerpan, Kedah. The iKERPAN has to deal with the White Spot Syndrome Virus, a kind or shrimp disease which affects the productions of the farm.The farm performs daily data collections, but the data are underutilized due to incapability of people to transform the data into much informative for quick decision makings.Thus, the goal of transferring knowledge of an analytical system is to assist the people to identify some problems that may harm the production of shrimp in systematic ways. The developed analytical system was developed in three main phases.Phase I involved several round table discussion among researchers to recognise the loopholes in data collection procedures and the analyses that had been practices.Next, extensive analytical system was performed in Phase II by transforming all the needed analyses and reports into a dashboard created using an Excel platform to allow for greater evidence based numerical analyses in much lower cost. Finally, series of testing were performed in Phase III to assess the reliability of the developed system in conjunction to the ultimate goal for identifying potential of occurrence of White Spot Syndrome Virus in production of shrimp.The developed dashboard is capable to gather all the needed information from the collected data in much systematic way and quick for review. Besides, it assists the production people to recognise an early signal for potential harm starting from the hatching process until the harvest period for every pond at the iKERPAN.